Examining the Impact of Wealth Redistribution through Zakat - Venkatesha Nayak; Kavya P. Hegde (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
As society considers it, it is scattered with distinct differences. If we highlight this issue, this gap is due to economic instability. Religion never differs between the rich and the poor, but the people who follow the religion will do, so as the fundamental thoughts, religion itself guides on the matter of removing the imbalance in religion in particular and society at large, for which we can find the taxing system in India. At the same time, Islam also proposes the idea of zakat to remove the gap between those who have and those who do not. To examine the idea of which the study was conducted by considering the Karnataka Zakat Trust of Mangaluru City of Karnataka state, as it is a donation that people are making out of their wealth. The information was gathered using a structured interview method, and for the remaining randomly selected 75 samples mail questionnaire was distributed, out of which 62 respondents responded to the study, so the total respondents of the study were 87 beneficiaries of Mangaluru City. This study shows that in the potential and globally recognized Mangaluru City, zakat is working effectively through Karnataka Zakat and Charitable Trust. Here, it is also proposed to claim the rebate for the relief of Islamic followers to make a difference in the country’s policy.